AN ELECTRON SCAN MICROSCOPE ANALYSIS RESULT OF DAMAGE ON WOOLLEN FIBER BY CLOTHES MOTH (TINEOLA BISSELLIELLA) (Mongolian Journal of Agricultural Sciences, 2015)
We have studied a type of damage on woollen fiber by clothes moths. 10 pieces of hurentser were put into each washed wool, raw wool and thick fiber of wool at the same temperature and did observation every 2 days. After 14 days, a number of dead and alive larvae, their length were noted down. Also we noted down that if they were moving or not and grew up or away. Samples were put in thermostat at 24.5 C. Each damage of every sample by clothes moth were not the same as each other.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 48-50